2022
DOI: 10.1007/s11524-021-00594-3
|View full text |Cite
|
Sign up to set email alerts
|

Strategies That Promote Equity in COVID-19 Vaccine Uptake for Black Communities: a Review

Abstract: Black communities have had a high burden of COVID-19 cases, hospitalizations, and death, yet rates of COVID-19 vaccine uptake among Blacks lag behind other demographic groups. This has been due in part to vaccine hesitancy and multi-level issues around access to COVID-19 vaccines. Effective strategies to promote vaccine uptake among Black communities are needed. To perform a rapid review covering December 2020–August 2021, our search strategy used PubMed, Google, and print media with a prescribed set of defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 11 publications
(13 reference statements)
2
99
0
Order By: Relevance
“…Disparities in vaccine uptake are attributed to multiple dimensions of structural inequality. Given historical and contemporary health care injustices, the African American (AA) population may not readily accept the COVID-19 vaccine as efficacious, safe, or accessible [ 6 , 7 ]. Moreover, recent studies have shown that misconceptions about the vaccine, mistrust in the health care system, and a lack of access to health services may discourage people from getting vaccinated, especially in communities of color [ 5 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Disparities in vaccine uptake are attributed to multiple dimensions of structural inequality. Given historical and contemporary health care injustices, the African American (AA) population may not readily accept the COVID-19 vaccine as efficacious, safe, or accessible [ 6 , 7 ]. Moreover, recent studies have shown that misconceptions about the vaccine, mistrust in the health care system, and a lack of access to health services may discourage people from getting vaccinated, especially in communities of color [ 5 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“… 40 Innovative approaches to engaging historically underserved groups in COVID-19 vaccination programs have emphasized that community-level engagement with religious groups, primary care facilities, and trusted community members can be more effective than physician-led efforts. 41 , 42 , 43 , 44 To understand next steps for patients who undergo gastrointestinal tract surgery and are discharged to hospice but are readmitted to the hospital, deeper review of clinical documentation to evaluate whether goals of care or advance care planning were attempted or not and even interviews with patients and/or their loved ones to understand positive and negative experiences around discussions will be essential. Importantly, our study uniquely identifies patients from communities with higher DCI as more likely to be readmitted to an acute care hospital after enrollment in hospice.…”
Section: Discussionmentioning
confidence: 99%
“…For in situations of scientific uncertainty, values guide us, and an infodemiologist who shares the values of the target audience can not only provide factual information where it exists but help guide the audience through the uncertainty according to the shared values of the group. In our cases, intervening in Black and Latinx communities, this often takes the form of advocating for obtaining vaccines as a powerful way to empower communities and address a long history of medical racism and as a community-focused way to show one's love for their neighbor and their community (Carson et al, 2021;Dada et al, 2022).…”
Section: Where Do Infodemiologists Intervene?mentioning
confidence: 99%